Swap Two Numbers without using Temp Variable

ArticlesLeave a Comment on Swap Two Numbers without using Temp Variable

Swap Two Numbers without using Temp Variable

That conclusion is definitely wrong. 

Your equation expanded equals: 
b = (a+b) – (a-b) = a+b – a + b = 2*b

For your example a=20, b=10
b = (20+10) – (20-10) = (30) – (10) = 20
b = 20 + 10 – 20 + 10 = 20

A counter example to disprove this: 
a=75, b=88

b = (75+88) – (75-88) = (163) – (-13) = 163 + 13 = 176

this equals the expanded algebraic expression :
b = (a+b) – (a-b) = a+b – a + b = 2*b
b = 75 + 88 – 75 + 88 = 88*2 = 176

It appears it was just coincidental that your example worked, not a mathematical truth. Good work trying to find a mathemagical short cut though.

Leave a Reply

Your email address will not be published. Required fields are marked *

Back To Top